Eksplorasi Etnomatematika Pada Solu Bolon Terhadap Konsep Geometri - Limasso Gultom; Niskah Pardede; Windhy F. Simamora; Ruth Mayasari Simanjuntak; Hardi Tambunan (Journal on Education, 2024)
This study aims to explore the geometric concepts present in the traditional construction of Solu Bolon, a traditional boat of the Batak Toba tribe in North Sumatra. Solu Bolon not only functions as a means of transportation but also as a symbol of social status and power in Batak Toba society. Through a qualitative descriptive ethnographic approach, this research identifies and analyzes the geometric elements found in the ornaments, construction process, and symbolism of Solu Bolon. Data were collected through observation, interviews with traditional leaders and Solu Bolon craftsmen, and visual documentation. The results of the study indicate that Solu Bolon applies various geometric concepts such as symmetry, proportion, and geometric shapes like rectangular prisms and beams in different parts of the boat, including the paddle blades, bow ornaments, stern decorations, and side walls. Additionally, this research found that the application of geometric concepts in Solu Bolon traditions can be used as a contextual approach in teaching geometry, thereby enhancing students' interest and understanding of geometry while fostering a sense of love and pride in local culture.